Negative association between plasma levels of adiponectin and polychlorinated biphenyl 153 in obese women under non-energy-restrictive regime - Mullerova, D; Kopecky, J; Matejkova, D; Muller, L; Rosmus, J; Racek, J; Sefrna, F; Opatrna, S; Kuda, O; Matejovic, M (International journal of obesity (2005), 2008)
The aim of this study was to reveal whether accumulation of the persistent organic pollutants (POPs), especially polychlorinated biphenyl (2,2',4,4',5,5'-hexachlorobiphenyl, PCB 153), affects plasma levels of adiponectin in obese patients. The study was designed as a longitudinal intervention trial with a control group, where 27 obese women (body mass index (BMI)>30 kg/m(2); age 21-74 years) were studied before (OB) and after (OB-LCD) a 3-month low-calorie-diet intervention (LCD; 5 MJ daily). As the control group, 9 female volunteers without LCD intervention were used (C; BMI=19-25 kg/m(2); age 21-64 years). Plasma levels of PCB 153 were measured by high-resolution gas chromatography with electron capture detection; total adiponectin and insulin plasma levels were quantified by immunoassays; and adiponectin multimeric complexes were quantified by immunoblotting. Plasma levels of total adiponectin, high and medium molecular weight multimers significantly negatively correlated with plasma levels of PCB 153 in OB, but not in C or in OB-LCD, whereas the LCD intervention lowered BMI by 3.3+/-3.0 kg/m(2). Our results may suggest suppression of adiponectin by PCB 153 in obese women under non-energy-restrictive regime, which may contribute to the known association of PCB 153 and other POPs with type 2 diabetes.
Keywords: Insulin; Young Adult; adiponektin; kalorická restrikce; biologické markery; polychlorované bifenyly; inzulin; longitudinální studie; Obesity; mladý dospělý; Biomarkers; Česká republika; látky znečišťující životní prostředí; obezita; Adult; Polychlorinated Biphenyls; Aged; dospělí; Case-Control Studies; senioři; Czech Republic; Caloric Restriction; lidé; ženské pohlaví; studie případů a kontrol; Humans; Body Mass Index; Adiponectin; Environmental Pollutants; Longitudinal Studies; index tělesné hmotnosti; Female; lidé středního věku; Middle Aged